Microbial cell factories à la carte: Elimination of global regulators Cra and ArcA generates metabolic backgrounds suitable for the synthesis of bioproducts in Escherichia coli - Egoburo, Diego Ezequiel (2018)
Manipulation of global regulators is one of the strategies used for the construction of bacterial strains suitable for the synthesis of bioproducts. However, the pleiotropic effects of these regulators can vary under different conditions and are often strain dependent. This study analyzed the effects of ArcA, CreC, Cra, and Rob using single deletion mutants of the well-characterized and completely sequenced Escherichia coli strain BW25113. Comparison of the effects of each regulator on the synthesis of major extracellular metabolites, tolerance to several compounds, and synthesis of native and nonnative bioproducts under different growth conditions allowed the discrimination of the particular phenotypes that can be attributed to the individual mutants and singled out Cra and ArcA as the regulators with the most important effects on bacterial metabolism. These data were used to identify the most suitable backgrounds for the synthesis of the reduced bioproducts succinate and 1,3-propanediol (1,3-PDO). The Δcra mutant was further modified to enhance succinate synthesis by the addition of enzymes that increase NADH and CO2 availability, achieving an 80% increase compared to the parental strain. Production of 1,3-PDO in the ΔarcA mutant was optimized by overexpression of PhaP, which increased more than twice the amount of the diol compared to the wild type in a semidefined medium using glycerol, resulting in 24 g · liter-1 of 1,3-PDO after 48 h, with a volumetric productivity of 0.5 g · liter-1 h-1.